SUPERVISI AKADEMIK KEPALA SEKOLAH DASAR DI ERA DIGITAL - Mustaqim, Anis; Nuryani, Lilis Kholisoh; Kusnandi, Kusnandi; Sumiati, Sumiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role and implementation of academic supervision by elementary school principals in the digital era and its implications for improving the quality of learning and teacher professionalism. The background of this study is based on the demands of educational transformation due to the development of digital technology, which requires principals to adapt more innovative and technology-based supervision practices. The method used is a literature review by analyzing various sources in the form of books, scientific journals, and relevant research results. Data collection techniques were carried out through searching, selecting, and analyzing the content of literature to obtain a comprehensive picture of academic supervision in the digital era. The results of the study indicate that academic supervision has shifted from a conventional approach to a more flexible, efficient, and sustainable digital approach. Technology-based supervision has been proven to improve teacher performance, pedagogical competence, and professionalism through the use of digital platforms and online learning systems. Furthermore, the success of supervision is greatly influenced by the adaptive, innovative, and collaborative leadership of principals. However, the implementation of academic supervision in the digital era still faces various challenges, such as limited infrastructure, low teacher digital literacy, and resistance to change. Therefore, a comprehensive strategy is needed through training, mentoring, and strengthening a technology-based school culture. Thus, academic supervision by school principals in the digital era plays a strategic role in continuously improving the quality of education.